2012
DOI: 10.1186/1471-2180-12-12
|View full text |Cite
|
Sign up to set email alerts
|

Dominance of multidrug resistant CC271 clones in macrolide-resistant streptococcus pneumoniae in Arizona

Abstract: BackgroundRates of resistance to macrolide antibiotics in Streptococcus pneumoniae are rising around the world due to the spread of mobile genetic elements harboring mef(E) and erm(B) genes and post-vaccine clonal expansion of strains that carry them.ResultsCharacterization of 592 clinical isolates collected in Arizona over a 10 year period shows 23.6% are macrolide resistant. The largest portion of the macrolide-resistant population, 52%, is dual mef(E)/erm(B)-positive. All dual-positive isolates are multidru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 44 publications
2
29
0
4
Order By: Relevance
“…One possibility for the mechanism is the production of fermentation metabolites such as ethanol and lactic acid that may be the actual causes of lifespan extension in the worm [73]. However, more recently, Gomez et al [74] showed that lactic acid produced by Q-less E. coli was not responsible for the life-span extension. Instead, they suggested that the survival rate of worms may be improved due to the delay in the colonization of the worm gut by respiratory-deficient bacteria as compared to the wild type bacteria.…”
Section: Other Micronutrientsmentioning
confidence: 99%
“…One possibility for the mechanism is the production of fermentation metabolites such as ethanol and lactic acid that may be the actual causes of lifespan extension in the worm [73]. However, more recently, Gomez et al [74] showed that lactic acid produced by Q-less E. coli was not responsible for the life-span extension. Instead, they suggested that the survival rate of worms may be improved due to the delay in the colonization of the worm gut by respiratory-deficient bacteria as compared to the wild type bacteria.…”
Section: Other Micronutrientsmentioning
confidence: 99%
“…QS is a method of social communication that enables bacteria to coordinate behavior of their community in a cell-density–dependent manner. QS systems rely on the synthesis of small signaling molecules (autoinducers), their passive diffusion or active transport across the cell envelope [11-13] and their receptor-mediated detection by members of the same species. In proteobacteria, these signals are most often N -acyl-L-homoserine lactones (AHL).…”
Section: Introductionmentioning
confidence: 99%
“…Este transposón se caracteriza por transportar los genes erm(B) y mef(E) debido a la adquisición del gen erm(B) en aislamientos del clon Taiwán 19F -ST236. Se ha planteado la hipótesis de que el CC271 ha emergido como un grupo 'clonal' exitoso a partir un linaje del clon Taiwán 19F -ST236 que contiene el Tn2010 y presentó reemplazo del tipo capsular como respuesta a la presión selectiva de la vacuna conjugada heptavalente (31)(32)(33). El Tn2010 ha sido reportado en Estados Unidos (33), China (32,34) y Venezuela (30).…”
Section: Discussionunclassified